Properties of Al-Ga alloys during cathodic polarization in NaF solution - Petar Ljumović; Antonija Višekruna (Zaštita Materijala)
In this paper, the electrochemical properties of high - purity aluminium with the addition of small amounts of gallium at high cathodic potentials have been investigated. The anodic current was followed through time in order to determine the quantity of charge needed for the formed substances oxidation. Anodic current responses for the period of 1 s were recorded. Time responses for the cathodic and anodic currents were recorded and showed in characteristic diagrams. The range of low and high cathodic potentials (LCP, HCP) was defined for all samples. For the experimental work, standard electrochemical cell with saturated calomel electrode (SCE) and platinum counter electrode were used. The solution 2 M NaF was used for this work.